Therapeutic efficacy of microwave coagulation versus liver resection for hepatocellular carcinoma within the Milan criteria: A propensity score matching analysis. Issue 2 (February 2022) - Feng, Hanxin; Yang, Chunbo; Xu, Feng; Zhao, Yang; Jin, Tianqiang; Wei, Zeyuan; Wang, Dexin; Dai, Chaoliu
Abstract: Introduction: This study aimed to compare the therapeutic efficacy of resection (RES) and microwave ablation (MWA) for hepatocellular carcinoma (HCC) within the Milan criteria. Materials and Methods: Between 2011 and 2019, 426 HCC patients within the Milan criteria were treated at our institution (RES: n = 291; MWA: n = 135). We compared overall survival (OS), disease-free survival (DFS), complications, and hospital stay in these patients using propensity score matching (PSM) and determined the prognostic factors using multivariate Cox analysis. Results: Following 1:1 matching using PSM, 121 patients were matched in each group. The 1-, 3-, and 5-year OS rates were 98.3%, 84.7%, and 69.6% for the MWA group and 96.5%, 81.8%, and 78.1% for the RES group (p = 0.667). The corresponding DFS rates for the MWA and RES groups were 81.8%, 54.4%, and 42.3% and 85.4%, 67.8%, and 57.9%, respectively (p = 0.174). The MWA group had less blood loss and shorter hospital stays (both p < 0.001) than the RES group. Conclusion: MWA resulted in survival outcomes that were similar to those of RES for HCC within the Milan criteria. However, it had more favorable hospital stay and blood loss outcomes than RES.